2019
DOI: 10.1101/690651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanics of MTOC clustering and spindle positioning in budding yeast Cryptococcus neoformans

Abstract: The mitotic spindle formation in pathogenic budding yeast, Cryptococcus neoformans, depends on multitudes of intertwined interactions primarily between kinetochores, microtubules (MT), spindle pole bodies (SPBs) and various molecular motors. Prior to spindle formation microtubule organizing centers (MTOCs), embedded on the outer nuclear envelope (NE), coalesce into a single SPB.We propose a 'grow-and-catch' model, in which cytoplasmic MTs (cMTs) nucleated by MTOCs grow and catch each other, to facilitate MTOC … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
(225 reference statements)
0
2
0
Order By: Relevance
“…Recent studies in C. neoformans have shown that the spatial distribution of dynein and Bim1 plays an essential role in nuclear migration (Varshney et al, 2019). As the cell cycle progresses, a localized dynein patch is formed in the daughter cortex along the axis of symmetry, which pulls the nucleus inside the daughter bud (Chatterjee et al, 2021). In our transcriptomic data, we observe that BIM1 transcript was at higher levels in slu7kd when compared wildtype while DYN1 transcript levels were unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in C. neoformans have shown that the spatial distribution of dynein and Bim1 plays an essential role in nuclear migration (Varshney et al, 2019). As the cell cycle progresses, a localized dynein patch is formed in the daughter cortex along the axis of symmetry, which pulls the nucleus inside the daughter bud (Chatterjee et al, 2021). In our transcriptomic data, we observe that BIM1 transcript was at higher levels in slu7kd when compared wildtype while DYN1 transcript levels were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent biochemical and cryo–EM studies have reported the role of LIS1/Pac1 in dynein regulation in S. cerevisiae (Markus et al, 2011; Huang et al, 2012; DeSantis et al, 2017). Studies in Cryptococcus neoformans have demonstrated the mechanics of nuclear migration and spindle positioning by time–lapse live cell imaging and quantitative modelling (Kozubowski et al, 2013; Varshney et al, 2019; Chatterjee et al, 2021). Transcriptional profiling of C. neoformans cell cycle revealed periodic changes in the expression of 1134 out of 6182 transcripts tested (Kelliher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%